Lateral force effects of three-axle locomotive bogie on track - Michálek, Tomáš; Haupt, Lukáš; Zelenka, Jaromír; Kohout, Martin; Liberová, Stanislava (My University, 2018)
This paper deals with guiding behaviour of a diesel-electric locomotive equipped with new three-axle bogies which were developed in co-operation of the company CZ LOKO and the Faculty of Transport Engineering of the University of Pardubice. At first, the design of the new bogie intended for the track gauge 1520 mm is shortly introduced. Then, the attention is paid to three different variants of secondary suspension design and their influence on lateral force effects of the locomotive on track in curves. The assessment is performed by means of the multibody simulation tool “SJKV” and it takes into account GOST standards. Possibilities of application of a system of active elements for bogie steering are also evaluated.
Příčné silové účinky třínápravového lokomotivního podvozku na trať
Keywords: three-axle bogie; secondary suspension; flexi-coil spring; tilting pad; active element; guiding force; GOST standards; safety against derailment; multi-body simulation; třínápravový podvozek; sekundární vypružení; flexi-coil pružina; naklápěcí podložka; aktivní prvek; vodicí síla; normy GOST; bezpečnost proti vykolejení; multi-body simulace